Antimicrobial Nanoemulsions for Pathogen Reduction in Fruits and Vegetables - J. A. Estefes-Duarte; G. Medina-Pérez; E. Morales-Luna; S. R. Pérez Ríos; A. J. Cenobio-Galindo; Pérez-Soto Elizabeth; U. González Lemus; L. N. Afanador-Barajas (Emerging Issues in Agricultural Sciences Vol. 4, 2023)
Postharvest losses of fruits and vegetables are because they are perishable products, which undergo considerable physiological changes during storage, such as the loss of organoleptic properties, the decrease in nutritional components, in addition to the loss of humidity that generates the softening of the tissue and consequently the rotting of the fruit, which leads to a concise, shelf life. Therefore, the product must reach its destination with the best quality characteristics such as appearance, color, flavor, texture, and the minimization of biological, chemical, and physical risks that affect human health. Postharvest losses affect many producers and exporters; conservation methods have been developed in recent years to prolong its useful life. In recent years, conservation methods such as controlled atmospheres, refrigeration techniques, chemical treatments, and coatings have been developed to combat these factors. Food coatings are thin layers of material that serve as a barrier between food and its environment during handling, processing, and storage. In recent decades, they have been widely studied and applied in foods such as peppers, mushrooms, tomatoes, and carrots, due to their low cost and environmentally friendly biological materials composition. They are classified into three categories: hydrocolloids, lipids, and compounds. Within lipid coatings, we find emulsified systems. Nanoemulsion is defined as a kinetically stable colloidal dispersion of two immiscible liquids. One is dispersed as small spherical particles with an r<100 nm in the other liquid. This chapter reviewed the formation process of nanoemulsion as coating, the functionality, the application of biocompounds to protect fruits and vegetables from microorganisms during storage, and the response of treated vegetal treated tissues.